Management of Moral Education in Increasing the Spiritual Intelligence of Santri - Achmad (Ta'dib, 2024)
This research aims to analyze moral values and their implementation in increasing the spiritual intelligence of santri. This study is a qualitative descriptive study with a phenomenological approach. Data were collected by means of interviews, observations, and documentation studies. Then the data were analyzed by data collection, data reduction, data presentation and conclusions/verification. The results of the study indicate that the values ​​of moral education implemented are the values ​​of Tawadlu’, discipline, honesty, and simplicity. Moral education is implemented with a management approach, namely planning, implementation, and supervision. Planning starts from deliberation to program determination. The implementation of moral education is integrated into scheduled Islamic boarding school programs such as muhadoroh kubro (public speaking) activities, deliberation, nadzaman, tasrifan, and other programs. Furthermore, moral education is evaluated during the activity (formative) and after the activity (summative).